Advanced in Computer Science and its Applications CSA 2013 - S. Obaidat, Mohammad; Jeong, Hwa Young; Yen, Neil Y.; Park, James J. (Jong Hyuk).; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The theme of CSA is focused on the various aspects of computer science and its applications for advances in computer science and its applications and provides an opportunity for academic and industry professionals to discuss the latest issues and progress in the area of computer science and its applications. Therefore this book will be include the various theories and practical applications in computer science and its applications.
Mobile and ubiquitous computing -- Dependable, reliable and autonomic computing -- Security and trust management -- Multimedia systems and services -- Networking and communications -- Database and data mining -- Game and software engineering -- Grid and scalable computing -- Embedded system and software -- Artificial intelligence -- Distributed and parallel algorithms -- Web and internet computing -- IT policy and business management.
Keywords: Engineering; Computer science; Software engineering; Engineering mathematics; Engineering; Appl.Mathematics/Computational Methods of Engineering; Computer Science, general; Software Engineering/Programming and Operating Systems